Ecological Development and Framework of Reverse Logistics System for Venous Industry Parks. Issue 1 (March 2021) - Xun, Wei; Cheng, Guoping; Wang, Chen
Abstract: Eco-industrial park has become the trend of the development of industrial parks in the world, and the shortage of resources is also a common problem faced by all countries, Combining the development of ecological parks with resource recycling and reuse is a current international hot spot. China has been exploring for more than 20 years, but in the complex social and economic system, the system mechanism of circular economy is still being explored, in which the construction of reverse logistics system has become a breakthrough. With the rapid development of information technologies such as the Internet of Things and mobile Internet, the venous Industry as a new form of circular economy is facing major opportunities. This article combines objective optimization and spatial analysis technology to explore the structure and operational performance of the reverse logistics system in the venous Industry, and provides useful countermeasures for the development of circular economy.